(untitled) (Historia, 2021)
English This article argues that the 1860s and 1870s represent an important transitional phase in the agrarian history of the Transvaal with regard to the relationship between white farmers and African labourers. Despite measures put in place by white settlers to secure labour, the availability of African labour emerged as a critical problem in this period and forced the Transvaal authorities to launch investigations into this matter. A number of causes can be identified. These include the discovery of diamonds on the southwestern Transvaal border in 1867, which created a huge demand for African labour and farm products; the emergence of markets in the towns and the transformation of production on white farms to more labour intensive, marketoriented farming. This situation was exacerbated by the inefficient application of labour stipulations; infighting between military officers and civil officials on labour matters and the presence of large semi-autonomous African communities in the outlying areas of the Transvaal, who were reluctant to provide labour. At least some of the factors that affected the labour demands of white settlers can also be traced back to the Cape Colony from which they had emigrated. African communities responded to the labour measures in various ways. For those in the central districts of the Transvaal migration appears to have been the most effective countermeasure. Afrikaans Blanke boere en swart arbeiders in pre-industriële Transvaal Hierdie artikel voer aan dat die sestiger- en sewentigerjare van die negentiede eeu ’n belangrike oorgangsfase in Transvaalse agrariese geskiedenis, met betrekking tot die verhouding tussen wit boere en swart arbeiders, verteenwoordig. Ten spyte van maatreëls deur die setlaars om arbeid te bekom, het die beskikbaarheid van swart arbeid in hierdie tydperk as ’n kritiese probleem na vore gekom en het dit die Transvaalse owerheid gedwing om ondersoek daarna in te stel. ’n Aantal oorsake kan geïdentifiseer word – onder andere die ontdekking van diamante aan die Transvaalse suidwestelike grens in 1867 wat ’n groot aanvraag vir swart arbeid en plaasprodukte geskep het; die opkoms van dorpsmarkte en die omskepping van produksie op plase na meer arbeidsintensiewe en markgeoriënteerde boerdery; die ondoeltreffende toepassing van arbeidsbepalings en onenigheid tussen militêre en siviele amptenare hieroor; en die teenwoordigheid van groot semi-outonome swart gemeenskappe in die afgeleë gebiede van Transvaal, wat teensinnig was om arbeid te verskaf. Ten minste sommige van die faktore wat die arbeidsaanvraag van die wit setlaars beïnvloed het, kan na die Kaapkolonie, vanwaar hulle geëmigreer het, teruggevoer word. Swart gemeenskappe het op verskillende wyses op arbeidsmaatreëls gereageer. Vir dié in die sentrale distrikte van Transvaal was migrasie klaarblyklik die mees doeltrefende teenmaatreël.